(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Rashtrakuta dynasty, which dominated large parts of the Indian subcontinent from the 8th to the 10th century CE, developed one of the most sophisticated and far reaching economic systems of early medieval India.